Bcl-2 and bax Expressions in pre-term, term and post-term placentas - Daher, Silvia; Guimarães, Alberto J.; Mattar, Rosiane; Ishigai, Márcia M.S.; Barreiro, Erica G.; Bevilacqua, Estela B. [UNESP] (Wiley, 2008)
Problem: Placental apoptosis-associated protein imbalance might contribute to the pathogenesis of pre- and post-term birth. Therefore, we evaluated the expression and distribution of pro-apoptotic (Bax) and anti-apoptotic (Bcl-2) molecules in term, pre-term and post-term placentas. Method of Study: Placental samples were collected from women with term (n = 25), pre-term (n = 7) and post-term (n = 10) deliveries. The expression of Bcl-2 and Bax was assessed by immunochemistry on paraffin-embedded placental specimens. Results: The pattern of immunostaining for Bcl-2 and Bax was the same in all samples, but not the intensity. The Bax/Bcl-2 ratio was higher in both pre-term and post-term placental samples compared with term placentas as a result of intense reactivity for the pro-apoptotic factor, Bax in pre-term and post-term placentas and, for Bcl-2 decrease in pre-term placentas. Conclusion: These findings suggest that different unbalance mechanisms in placental apoptotic-associated protein expressions may be involved in the physiopathology of pre-term and post-term births. © 2008 The Authors Journal compilation © 2008 Blackwell Munksgaard.
Keywords: Apoptosis; Parturition; Placenta; Post-term birth; Premature labor